2015
DOI: 10.1002/pon.3807
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward disclosure of medication side effects: a nationwide survey of Korean patients, caregivers, and oncologists

Abstract: Background: We aimed to compare the views of cancer patients, family caregivers, and oncologists about the disclosure of side effects in respect to their probability of occurrence, severity, and treatment purpose. We also compared attitudes toward potential harm of side effect disclosure, patients' perceived ability to understand the risk of the side effects, and informed decision-making regarding side effects.Methods: A national survey was performed with 750 patient-caregiver dyads (75.5% participation rate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In contrast, doctors felt they give an adequate amount of information about medication and risk, based on their personal assessment of their patients, which may well reflect their own biases and exacerbate inequity [60]. These findings are consistent with previous research exploring patients' and doctors' attitudes towards information sharing [61][62][63][64][65]. As has been found elsewhere, doctors in our study typically found it difficult to communicate risk [66][67][68].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, doctors felt they give an adequate amount of information about medication and risk, based on their personal assessment of their patients, which may well reflect their own biases and exacerbate inequity [60]. These findings are consistent with previous research exploring patients' and doctors' attitudes towards information sharing [61][62][63][64][65]. As has been found elsewhere, doctors in our study typically found it difficult to communicate risk [66][67][68].…”
Section: Discussionsupporting
confidence: 87%
“…In one survey, patients felt that information about severe side effects was more important than information about mild side effects. 16 When patients had to rate the importance of information about side effects (‘0 = not important at all’; ‘100 = extremely important’), the average response was 84 and 63 for major and minor side effects, respectively, 26 similarly implying that information about severe side effects was more important than mild side effects. Likewise, a survey found that 44% wanted to be informed of a severe very rare side effect, and only 28% of a mild very rare side effect.…”
Section: Attitudes Towards Side Effect Informationmentioning
confidence: 99%
“…Furthermore, a consistent minority, averaging around 10% (ranging from 0.4% to 42%) does not want any information about side effects. 15,16,1921,2325 One reason for patients wanting no or little information about side effects seemed to be that ‘ignorance is bliss’. 25…”
Section: Attitudes Towards Side Effect Informationmentioning
confidence: 99%
See 2 more Smart Citations